2022
DOI: 10.1155/2022/7060766
|View full text |Cite
|
Sign up to set email alerts
|

Status of Soil Acidity under Different Land Use Types and Soil Depths: The Case of Hojje Watershed of Gomibora District, Hadiya Zone, Southern Ethiopia

Abstract: In the humid regions of Ethiopia, soil productivity and fertility are significantly affected by soil acidity, which is connected to infertility and mineral toxicity. The study aimed to assess the status of soil acidity under different land use types and soil depths in Hojje watershed of Gomibora district, Hadiya Zone, Southern Ethiopia, in November 1, 2020. Soil samples (24 nos.) were collected using X-design format from four different land use typeshome garden, cultivated land, grazing land, and Eucalyptus pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…However, soil pH at the study site was acidic (Table 1). Intensive agriculture leads to soil acidification (decrease in pH) (Abure 2022) and is a sign of land degradation in a watershed (Felix et al 2015). Total Pb in the soil was below the maximum Pb level, which is considered dangerous for agricultural activities (CCME -Canadian Council of Ministers of the Environment 1999).…”
Section: Results and Discussion Study Site Characteristicsmentioning
confidence: 99%
“…However, soil pH at the study site was acidic (Table 1). Intensive agriculture leads to soil acidification (decrease in pH) (Abure 2022) and is a sign of land degradation in a watershed (Felix et al 2015). Total Pb in the soil was below the maximum Pb level, which is considered dangerous for agricultural activities (CCME -Canadian Council of Ministers of the Environment 1999).…”
Section: Results and Discussion Study Site Characteristicsmentioning
confidence: 99%
“…Ca), exchangeable Potassium (Exch. K), available Phosphorus (P), total soil Nitrogen (N), base saturation (BS) and cation exchange capacity (CEC), as documented by several studies (Abure, 2022;Bouajila et al, 2023). Nonetheless, the paramount application, that is, red mud combined with cow manure (T3R3), culminated in a notable decline in the aforementioned parameters while simultaneously escalating soil pH, exchangeable magnesium (Exch.…”
Section: Discussionmentioning
confidence: 99%
“…This is claimed by Nair, Kumar [15] in that there is little availability of surface and subsurface acidity in the forest and coffee landscape as compared to rubber and coconut land use practices. Abure [16] reported that acidity of soil under home garden was better than eucalyptus plantation land use. This indicated that proper species screening for acidity amelioration technique is pertinent issues.…”
Section: Introductionmentioning
confidence: 99%